HISTOPATHOLOGY LIVER AND KIDNEY OF Clarias gariepinus THAT ARE FED SIMPLISIA MANGOSTEEN RIND (Garcinia mangostana L) - Kahfi, Khaiqal El; Riauwaty, Morina; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study has been conducted on Maret to June 2016 in at Parasite and Fish DiseaseLaboratory, Faculty of Fisheries and Marine Sciences, University of Riau. Theaims of this study was to know changes in liver and kidney tissue structures of catfish(Clarias gariepinus) fed simplisia mangosteen rind. This study used an experimentalmethod and histological of the liver and kidney structure of Clarias gariepinus wereanalyzed by descriptive. The treated fishes were fed in three differentconcentrations of fed simplisia mangosteen rind. Kn: (feed control) the fish were notfed simplisia mangosteen rind, P1: The fish were fed simplisia mangosteen rind 2g/kg, P2: The fish were fed simplisia mangosteen rind 4 g/kg, P3: The fish were fedsimplisia mangosteen rind 6 g/kg and fishes were reared for 60 days. Showed that theabnormalities of liver and kidney such us inflammatory cells, haemorrhage,h yp e r t r h o p y and necrosis. Base on data obtain it can be concluded that the bestconcentration of simplisia mangosteen rind 2 g/kg is able to prevent damage of liverand kidney after given fed simplisia mangosteen rind.Key words : Clarias gariepinus, simplisia mangosteen rind, histopathology,kidney, liver